Beyond Guidelines: Early DCB Intervention and Plant-Based Diet as Lifesaving Strategies - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
We present a case involving a 48-year-old asymptomatic male with a constellation of coronary artery disease (CAD) risk factors, including obesity, hypertension, untreated hyperlipidaemia, untreated prediabetes, and a significant family history of premature CAD. An initial assessment performed at an external facility via computed tomography coronary angiography (CTCA) revealed a moderate stenosis within the left circumflex artery (LCX), which was subsequently confirmed as an 80% luminal narrowing by invasive coronary angiography (ICA). Since a fractional flow reserve (FFR) greater than 0.8 was obtained, the decision was made to defer percutaneous coronary intervention (PCI) and manage conservatively with optimal medical therapy (OMT), albeit without structured lifestyle modification guidance. Three months following this initial evaluation, the patient presented emergently to Bethsaida Hospital under the care of Prof. Dasaad Mulijono with an acute myocardial infarction (AMI) due to acute total occlusion (100%) of the LCX with reduced LV (EF of 40%). Following emergent PCI, an aggressive lifestyle intervention strategy, encompassing stringent metabolic optimization and a transition to a plant-based diet (PBD), was initiated. This integrative approach yielded substantial clinical improvements. At one-year follow-up, the patient's left ventricular ejection fraction (LVEF) had markedly improved to 60%, and he exhibited no clinical symptoms indicative of ischemia or heart failure. This clinical scenario highlights the critical implications of underrecognized vulnerable plaques (VPs), inadequate assessment of patient vulnerability, and insufficient communication between patients and providers during initial therapeutic decision-making. This case report highlights the substantial therapeutic potential of comprehensive lifestyle modifications, particularly a PBD, in reversing the progression of atherosclerosis, mitigating restenosis, and improving outcomes in heart failure. Additionally, we propose critical considerations supporting the early utilization of drug-coated balloon (DCB) angioplasty for coronary lesions exhibiting stenosis <90%, especially in patients likely to exhibit suboptimal adherence to medical therapy alone.